A new species of the porcelain crab genus Petrolisthes from the Pacific coast of Panama, with taxonomic notes on closely related species (Decapoda: Anomura: Porcellanidae) - de Azevedo Ferreira, Luciane Augusto; Santana-Moreno, L. Daniel; Anker, Arthur (Zootaxa, 2020)
A new species of porcelain crab, Petrolisthes lazarus sp. nov., is described from the Paciﬁc coast of Panama, based on two female specimens. The new species is morphologically most similar to another eastern Pacific species, P. crenulatus Lockington, 1878, especially in the general configuration of the carapace, chelipeds and ambulatory legs. However, P. lazarus sp. nov. can be separated from P. crenulatus by the differences in the proportions of the carapace, the shape of the frontal region of the carapace, and the setation pattern of the cheliped. In addition, P. lazarus sp. nov. and P. crenulatus appear to be allopatric, the latter species presently being known only from Mexico. Among other eastern Pacific taxa, P. lazarus sp. nov. may have some affinities with P. ortmanni Nobili, 1901 and P. lewisi (Glassell, 1936), from which it can be easily distinguished by the chelipeds lacking a dense field of setae on the outer (lateral) surface of the palm and with different proportions of some articles, especially the carpus. The four species can also be distinguished from each other by their diagnostic, although somewhat variable colour patterns.